2015
DOI: 10.1051/0004-6361/201425367
|View full text |Cite
|
Sign up to set email alerts
|

TheGaia-ESO survey: Discovery of a spatially extended low-mass population in the Vela OB2 association

Abstract: The nearby (distance ∼ 350-400 pc), rich Vela OB2 association, includes γ 2 Velorum, one of the most massive binaries in the solar neighbourhood and an excellent laboratory for investigating the formation and early evolution of young clusters. Recent Gaia-ESO survey observations have led to the discovery of two kinematically distinct populations in the young (10-15 Myr) cluster immediately surrounding γ 2 Velorum. Here we analyse the results of Gaia-ESO survey observations of NGC 2547, a 35 Myr cluster located… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 29 publications
(40 reference statements)
6
19
0
Order By: Relevance
“…The first stellar component is found to be 1 to 2 Myr older, and is probably more centrally concentrated around g 2 Vel. A kinematically distinct component was also found in the young (∼35 Myr) cluster NGC 2547, also in Vela OB2, which appears more similar to one of the g 2 Vel components (Sacco et al 2015). These studies depict a young, low-mass stellar population spread over several square degrees in the Vela OB2 association.…”
Section: Clustering On Gmc Scalessupporting
confidence: 54%
See 1 more Smart Citation
“…The first stellar component is found to be 1 to 2 Myr older, and is probably more centrally concentrated around g 2 Vel. A kinematically distinct component was also found in the young (∼35 Myr) cluster NGC 2547, also in Vela OB2, which appears more similar to one of the g 2 Vel components (Sacco et al 2015). These studies depict a young, low-mass stellar population spread over several square degrees in the Vela OB2 association.…”
Section: Clustering On Gmc Scalessupporting
confidence: 54%
“…The first, studied by Jeans (1902), 8 addresses the balance between self-gravity and thermal pressure. The second scale results from the analysis by Toomre (1964), originally studied by Safronov (1960), which considers also shear forces from differential rotation in addition to gravity and pressure. In a galaxy with a global stellar spiral density wave or a stellar ring, large scale dynamics lead to gaseous structures like the so-called beads on a string and spurs (e.g., Renaud et al 2014;Schinnerer et al 2013).…”
mentioning
confidence: 99%
“…This bonanza of physical puzzles is closely linked with compact object formation by corecollapse supernovae (e.g., Eldridge and Tout, 2004;Özel et al, 2010;Perego et al, 2015;Sukhbold et al, 2016;Suwa et al, 2015;Timmes et al, 1996) and the diversity of observed massive star transients (e.g., Ofek et al, 2014;Smith et al, 2016;Van Dyk et al, 2000). Recent observational clues that challenge conventional wisdom (Boggs et al, 2015;Jerkstrand et al, 2015;Strotjohann et al, 2015;Vreeswijk et al, 2014;Zavagno et al, 2010), coupled with the expectation of large quantities of data from upcoming surveys (e.g., Creevey et al, 2015;Papadopoulos et al, 2015;Sacco et al, 2015;Yuan et al, 2015), new measurements of key nuclear reaction rates and techniques for assessing reaction rate uncertainties Wiescher et al, 2012), and advances in 3D pre-SN modeling (Couch et al, 2015;Jones et al, 2017;Müller et al, 2016), offer significant improvements in our quantitative understanding of the end states of massive stars.…”
Section: B Helium Burning In Massive Starsmentioning
confidence: 99%
“…The observations started at the end of 2012, the raw spectra are quickly made public on the ESO archive, and the advanced data products (fully reduced spectra, radial velocities and stellar parameters including abundances) are following on a fastpaced schedule. There are plenty of examples of science results from this project (e.g., Magrini et al 2015;Lind et al 2015;Sacco et al 2015).…”
Section: Ongoing Projectsmentioning
confidence: 99%